Алелопатична активність ґрунту в ризосфері Echinacea purpurea (L.) Moench та Silybum marianum (L.) Gaertn. - Shevchuk, O.M.; Ahurova, I.V.; Kokhan, T.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
Allelopatic activity of soil in the Echinacea purpurea (L.) Moench and Silybum marianum (L.) Gaertn is investigated. It is determined that the both species rhizospheric soil has high allelopathic activity. Silybum marianum’s soil inhibits the development of the seedlings Agropyron pectinatum (M. Bieb.) Beauv. and is neutral for Festuca regeliana Pavl. It is shown growth stimulation of the seedlings Agropyron pectinatum and Festuca regeliana on the rizospheric soil of Echinacea purpurea that is shown expediency of that species joint sowing.